2022
DOI: 10.1007/s12565-022-00652-z
|View full text |Cite
|
Sign up to set email alerts
|

Double-layered two-directional somatopleural cell migration during chicken body wall development revealed with local fluorescent tissue labeling

Abstract: The ventral body wall is derived from the somatic layer of the lateral plate mesoderm, somatopleure, and somite. The primary ventral body wall is formed as a result of the lateral growth of the somatopleure. The secondary body wall is generated through the migration of somitic cells into the somatopleure. While it is reported that the cervical somatopleural cells migrate caudally to the thoracic region during body wall development, the migration of the thoracic somatopleural cells has not been elucidated. To i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In confirmation of this, we found the intermyotomal spaces distal to the rib anlagen largely free of somite cells (Figure 8 ), indicating that they are corridors for the elongation of the Sox9‐positive rib anlagen. Recent cell labelling studies have shown that the growing sternal rib anlagen are accompanied by dynamic populations of somatopleural cells (Sakamoto et al, 2022 ), indicating that these corridors are not cell‐free regions, but that the invading somite cells rather supplant the somatopleural cells during extension.…”
Section: Discussionmentioning
confidence: 99%
“…In confirmation of this, we found the intermyotomal spaces distal to the rib anlagen largely free of somite cells (Figure 8 ), indicating that they are corridors for the elongation of the Sox9‐positive rib anlagen. Recent cell labelling studies have shown that the growing sternal rib anlagen are accompanied by dynamic populations of somatopleural cells (Sakamoto et al, 2022 ), indicating that these corridors are not cell‐free regions, but that the invading somite cells rather supplant the somatopleural cells during extension.…”
Section: Discussionmentioning
confidence: 99%